2016
DOI: 10.1111/aas.12753
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute kidney injury on patient outcome in out-of-hospital cardiac arrest: a prospective observational study

Abstract: Kidney disease occurred in about half of patients successfully resuscitated from OHCA. Presence of AKI, but not RRT, was associated with unfavourable 6-month outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 38 publications
5
32
1
Order By: Relevance
“…However, many factors should be considered in evaluating the results of the current study. First, there were differences in the baseline characteristics of the study cohorts between the present study and previous ones (e.g., age, male sex, witnessed arrest, bystander CPR, time from CPR to ROSC, and shock after ROSC) [3,4,10,11]. Second, there are insufficient data to determine absolute indications and the optimal timing for initiation of RRT.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…However, many factors should be considered in evaluating the results of the current study. First, there were differences in the baseline characteristics of the study cohorts between the present study and previous ones (e.g., age, male sex, witnessed arrest, bystander CPR, time from CPR to ROSC, and shock after ROSC) [3,4,10,11]. Second, there are insufficient data to determine absolute indications and the optimal timing for initiation of RRT.…”
Section: Discussionmentioning
confidence: 67%
“…In previous studies, the mortality of the RRT group was not lower than that of the non-RRT group [3,4,10,11]. Winther-Jensen et al reported that the 30-day mortality of a RRT group was significantly higher than that of a non-RRT group in the cohort of OHCA patients [11].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Presence of post-arrest AKI is associated with unfavourable outcome, and the chance of survival is reduced proportional to the severity of AKI disease [2]. Despite this, one study showed that OHCA patients treated with RRT had a relatively good prognosis, as 50% were alive after six months, with 89% having good neurological outcome [3].Although there are few clinical studies on AKI after CA, we know that AKI often is associated with hypervolaemia, hyperkalaemia and acidosis, and tight control of these factors may be important in the initial phase after CA. Delayed awakening from coma may be expected in post-arrest AKI due to reduced renal clearance of analgesics and sedatives, and development of uremic encephalopathy.…”
mentioning
confidence: 99%